2020
DOI: 10.33369/jeet.4.3.368-385
|View full text |Cite
|
Sign up to set email alerts
|

The Expressive Speech Act on Ridwan Kamil’s Comments in Instagram Posting about First COVID-19 Case in Indonesia

Abstract: In the early time of the president’s announcement about the first patient infected the Coronavirus in Indonesia, a governor of West Java, Ridwan Kamil, uploaded the information of the president’s announcement in his Instagram account @ridwankamil. The Instagram post received many comments as responses from his followers. Regarding the issue, this study aims at seeing the netizens' responses to the news about the first patient who infected the Coronavirus in Indonesia, Ridwan Kamil posted on Instagram through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Disasters and diseases affect the way people communicate and the language they use. In this regard, some studies have sought this during the COVID-19 pandemic ( Anggraeni et al, 2020 ; Park et al, 2021 ; Iqbal et al, 2020 ). Nevertheless, many of the previous studies have focused on analysing speech acts in the political context.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Disasters and diseases affect the way people communicate and the language they use. In this regard, some studies have sought this during the COVID-19 pandemic ( Anggraeni et al, 2020 ; Park et al, 2021 ; Iqbal et al, 2020 ). Nevertheless, many of the previous studies have focused on analysing speech acts in the political context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, many of the previous studies have focused on analysing speech acts in the political context. For example, Anggraeni et al (2020) explored the expressive speech act on the president's announcement about the first patient infected with COVID-19 in Indonesia through sampling comments on Instagram. A qualitative and descriptive research analysis of the data showed that responses on Instagram were categorized into 16 speech acts of wishing, 9 complaining acts, and 4 protesting acts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the coronavirus outbreak, numerous studies have been carried out throughout the world concerning various aspects of speech acts. Some are studies investigating the use of speech acts, as in Nurkhamidah (2020); Phatthanasutinon and Rattanadilok Na Phuket (2021), while some are studies focusing on specific types of speech acts, as in Al-Azzawi and Majeed (2020); Anggraeni et al (2020); Ogiermann and Spyridoula (2021). Phatthanasutinon and Rattanadilok Na Phuket (2021) analyzed press conferences held by the Centre for COVID-19 Situation Administration and broadcast on the "Thai Ku Fah Government House" YouTube channel between March, 26 and April, 30 2020.…”
Section: Related Studiesmentioning
confidence: 99%
“…Al-Azzawi and Majeed (2020) investigated the use of advising, examples of which were categorized as directives, in COVID-19 instructions. Anggraeni et al (2020) analyzed comments on an Instagram post made by Ridwan Kamil, the governor of West Java, Indonesia, about that country's President's announcement concerning the first patient infected with the coronavirus in Indonesia. The findings detected expressive speech acts of wishing, complaining, and protesting related to COVID-19.…”
Section: Related Studiesmentioning
confidence: 99%
“…Instagram's advantage over other social media applications lies in visual content. During the COVID-19 pandemic in Indonesia, Instagram uses for campaigning and socializing health protocols by the government through the Ministry of Health (Nasution, 2020), Ministry of Communication and Informatics (Hani&Oktavianti,2021), Regional Heads (Anggraeni & Soemantri, 2020). It is used as a communication medium from the online community kawalcovid19.…”
Section: Instagram As a Communication Media During The Covid-19 Pandemicmentioning
confidence: 99%